2019
DOI: 10.1590/1981-52712015v43n1rb20180045
|View full text |Cite
|
Sign up to set email alerts
|

Conhecimento de Alunos de Medicina do Centro Universitário do Estado do Pará sobre a Residência Médica

Abstract: A residência médica (RM) é um curso de pós-graduação cujo ensino se baseia principalmente na prática voltada a determinada especialidade. Ao decidir se especializar, o acadêmico de Medicina precisa entender como funciona o processo de seleção, o número de vagas, as fases, a necessidade de se matricular em um curso preparatório para residência, quais as especialidades de cada serviço, seus pontos negativos e positivos, entre outros aspectos. Dessa forma, este estudo tem como objetivo identificar o conhecimento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 5 publications
0
4
1
3
Order By: Relevance
“…On the other hand, the ISAPPC-MED synthetic index indicates that municipal public institutions show less adherence in relation to other types of administration. This finding is in contrast with the result of the study by Oliveira et al 23 , which compared the PPCs of medical courses in public institutions at the municipal and federal levels, showing that there were no differences between them. Because this study has a national scope, innovation of data is observed, as well as relevant information for future studies.…”
Section: National Performance By Type Of Institution and By Macro-reg...contrasting
confidence: 99%
“…On the other hand, the ISAPPC-MED synthetic index indicates that municipal public institutions show less adherence in relation to other types of administration. This finding is in contrast with the result of the study by Oliveira et al 23 , which compared the PPCs of medical courses in public institutions at the municipal and federal levels, showing that there were no differences between them. Because this study has a national scope, innovation of data is observed, as well as relevant information for future studies.…”
Section: National Performance By Type Of Institution and By Macro-reg...contrasting
confidence: 99%
“…Em contrapartida, o ISAPPC-MED mostra que as instituições públicas municipais revelam menor aderência às outras formas de administração. Tal achado se contrapõe ao resultado do estudo de Oliveira et al 23…”
Section: Performance Nacional Por Tipo De Instituição E Por Macrorreg...unclassified
“…They may occasionally obtain a license in plastic surgery, following a review of their knowledge and experience by the medical association. 24 It can be noted that a generalist profile is very common among physicians in small towns, while in big cities there is greater demand for specialized professionals.…”
Section: Medical Specialty Title In Plastic Surgerymentioning
confidence: 99%
“…These findings are similar to previous findings regarding the prevalence of confidential disciplinary sanctions. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] The data shows that punishment C was applied most to doctors aged 30-39 (the youngest group), and punishment E was applied most to doctors aged 70 and over (the oldest group).…”
Section: Disciplinary Sanctionsmentioning
confidence: 99%